ENVIRONMENTAL PROTECTION AND THE NEW SAFEGUARDS PROVIDED IN DIRECTIVE (EU) 2024/1203 ON THE PROTECTION OF THE ENVIRONMENT THROUGH CRIMINAL LAW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The research carries out an in-depth analysis of Directive (EU) 2024/1203 of the European Parliament and of the Council of 11 April 2024 on the protection of the environment through criminal law and replacing Directives 2008/99/EC and 2009/123/EC as a normative instrument for criminal environmental protection within the European Union. The Directive is a reaction to the growing environmental crime with a transnational dimension, requiring complex and modern measures for prevention and punishment. The main practical challenges arising from the transposition and application of the Directive are outlined. The conclusion of the study underlines that in order to achieve the objectives of the Directive and the effectiveness of the measures envisaged, it is not only necessary to harmonize legislation, increase the capacity of law enforcement and investigative authorities and enhance international cooperation, but it is essential to develop standardized investigative methods in relation to the different environmental crimes, taking into account their specificities. Efforts in this direction are indeed worthwhile, because the objective pursued is the protection of the environment, so important to our existence.